Actinobacillus vicugnae sp. nov., isolated from alpaca (Vicugna pacos). Issue 10 (8th August 2019) - Kirchner, Miranda; Hunt, Brian; Carson, Therese; Duggett, Nicholas; Muchowski, Jakub; Whatmore, Adrian M.
Abstract : Ten strains of an Actinobacillus -like organism were isolated from alpaca ( Vicugna pacos ) in the UK over a period of 5 years, with no known epidemiological linkages. The isolates are distinct, based on both phenotype and genotype, from any previously described Actinobacillus species. Molecular analysis, based on 16S rRNA, rpoB and infB gene sequences, placed the isolates as a novel, early branching, lineage within the currently recognised Actinobacillus sensu stricto . In agreement with the results of the single-gene analysis, average nucleotide identity values, based on whole genome sequences, showed very similar identities to a number of members of the Actinobacillus sensu stricto notably Actinobacillus equuli, Actinobacillus suis and Actinobacillus ureae . At least two phenotypic characteristics differentiate the alpaca isolates from other Actinobacillus sensu stricto species, and from taxa likely falling within this group but awaiting formal species description, with Actinobacillus anseriformium and A. equuli subsp. haemolyticus being the most closely related phenotypically. The alpaca isolates can be differentiated from A. anseriformium by production of β-galactosidase (ONPG) and acid from raffinose, and from A. equuli subsp. haemolyticus by production of acid from d -sorbitol and failure to produce acid from d -xylose. Isolates were obtained from multiple sites in alpaca including respiratory tract, alimentary tract and internal organs although further evidence is required to understand any pathogenic significance. Based on the results of characterization described here, it is proposed that the isolates constitute a novel species, Actinobacillus vicugnae sp. nov. The type strain is W1618 T (LMG30745 T NCTC14090 T ) isolated in the UK in 2012 from oesophageal ulceration in an alpaca ( Vicugna pacos ).